RAM analysis of crude oil transfer pumps using dominant failure mode - Mokhtar, A.A. (Asian Research Publishing Network, 2016)
A good maintenance strategy requires a good reliability, availability and maintainability (RAM) analysis in order to cater the real problem to specific equipment or a system. Resolving the real problem will improve the equipment/system reliability to ensure higher availability of the system to operate. In this paper, two crude oil transfer pumps were selected for RAM analysis. The analysis was done based on individual dominant failure mode that contributed to failures of the pumps. Firstly, reliability and maintainability analysis were carried out to obtain the required parameters. Then, reliability block diagram (RBD) was constructed and simulated to obtain the availability of the crude oil transfer pump system. This analysis can help to identify critical failure modes that affect the system reliability which directly affect the operational availability of the pump system. Â© 2006-2016 Asian Research Publishing Network (ARPN).